IMPORTANCE-PERFORMANCE ANALYSIS OF PT PELINDO TERMINAL PETIKEMAS' CORPORATE IMAGE - Nugraha Kusbianto; Ute Chairuz M. Nasution; V. Rudy Handoko; Ayun Maduwinarti (DIA: Jurnal Administrasi Publik, 2023)
Corporate image is an important factor that can affect the performance of a company. PT Pelindo Terminal Petikemas (SPTP) is one of the subholdings of PT Pelindo that operates the container terminal business in Indonesia. This study aims to identify the factors of corporate image that are important to stakeholders and how PT SPTP performs in meeting those factors. The study used the importance-performance analysis (IPA) method with a questionnaire as the data collection instrument. The respondents were internal stakeholders (structural employees, non-structural employees, and shareholders) and external stakeholders (academics, members of the DPR RI, relevant associations, customers, government agencies, journalists, partner companies, CSR recipients, and vendors). The results of the study showed that the factors of corporate image that are important to PT SPTP stakeholders are: Company reputation, Business ethics, Social and environmental responsibility, Positive feelings, Usefulness, PT SPTP has met most of these factors. However, there are still some factors that need to be improved, namely: Communication of social and environmental responsibility, and Communication of company activities. This study is expected to provide information to PT SPTP to improve its corporate image.